Analisis keterampilan proses sains Siswa kelas 4 SD 03 Pecangaan pada pembelajaran tatap muka - Edy Kurniansah; Siti Masfu’ah; Mila Roysa (COLLASE (Creative of Learning Students Elementary Education), 2023)
Learning has now been carried out face-to-face 100% by prioritizing the development of potential in the form of students' knowledge, attitudes, and skills. It is also necessary to balance these three aspects so as to create a dignified civilization. This study aims to analyze students' science process skills in face-to-face learning in class IV SDN 03 Pecangaan. In this study, the researcher used a quantitative approach or type of research, while for data collection, the survey data collection method was used. The samples in this study were students of SDN 03 Pecangaan, Jepara Regency, class IV A, totaling 38 students and class IV B students totaling 36 students. Data collection techniques in this study were interviews, questionnaires, and documentation. Data analysis techniques in this study are normality test and hypothesis testing. The results showed that the students' science process skills in face-to-face learning in class IV SDN 03 Pecangaan as a whole resulted in an average achievement of 41% in the medium category. With the medium category, the conclusion obtained is that some students are less able to carry out activities in science process skills.